Reply to Comment by S. Helama and V. V. Matskovsky on"Absence of Age‐Related Trends in Stable Oxygen Isotope Ratios From Oak Tree Rings". Issue 2 (11th February 2020) - McCarroll, Danny; Duffy, Josie E.; Loader, Neil J.; Young, Giles H.F.; Davies, Darren; Miles, Daniel; Ramsey, Christopher Bronk
Abstract: We thank Helama and Matskovsky (2019, https://doi.org/10.1177/0959683616652709) for their interest in our work. They argue that we should use Regional Curve Standardization (RCS) to identify trends in our oxygen isotope series and to detrend them prior to climate reconstruction. We disagree. Key Point: There is no evidence for age trends in the stable oxygen isotope ratios and thus no need for de‐trending of any kind